Spatial Resolution Enhancement of Satellite Hyperspectral Data via Nested Hypersharpening With Sentinel-2 Multispectral Data - Alparone, Luciano; Arienzo, Alberto; Garzelli, Andrea (IEEE journal of selected topics in applied earth observations and remote sensing, 2024)
This article presents an original method for the spatial resolution enhancement of satellite hyperspectral (HS) data by means of the Sentinel-2 visible and near infrared (VNIR) and short-wave infrared bands at 10 and 20 m spatial resolution. Presently, HS data are available from PRISMA (Italian acronym for HS precursor of the application mission) and Environmental Mapping and Analysis Program (EnMAP): both map the spectral interval of the solar radiation onto 240 and 224 bands, respectively, with 10 and 6.5/10 nm widths. A 5 m × 5 m panchromatic (PAN) band is also acquired by PRISMA. When the PAN band is unavailable, or better, the higher spatial resolution sharpening band is not unique, advantage can be taken from the hypersharpening protocol. First, the 20-m bands of Sentinel-2 are hypersharpened to 10 m by means of the four 10-m VNIR bands of the same instrument. Then, the 10-m hypersharpened bands of Sentinel-2 are used to sharpen the 30-m bands of PRISMA at 10 m as well, still according to the hypersharpening protocol. Eventually, the 10- m hypersharpened bands are pansharpened at 5 m by means of the PAN image, if available. Results show that for PRISMA the nested hypersharpening followed by pansharpening is better than plain HS pansharpening, both visually and according to full-scale indexes of spectral and spatial consistence. For EnMAP data, in which the PAN image is missing, the improvement of the fused data with respect to the original EnMAP and Sentinel-2 data has been quantified by means of two novel statistical indexes capable of measuring the spatial and intersensor consistencies between sharpened and sharpening data.